The Practice of English Language Teaching - Harmer, Jeremy (Pearson Education Limited, 2015)
The Practice of English Language Teaching is the essential guide for teachers of English. It explains current pedagogy to teachers who want to access the more relevant ELT practices and incorporate them into their lessons. The fifth edition has been revised to reflect the latest development in language teaching. English language classrooms have changed greatly since the first edition of this book was published, more than thirty years ago. Advances in the technology available to teachers and students, both inside and outside the classroom, have brought about some of the most noticeable of these changes. However, the fundamental questions of how best to teach and learn a language remain the same. This book is informed by past theory and practice and by books and articles written by teachers and researchers in recent years. It examines current issues such as the lingua franca core, teaching unplugged and the rise of digital testing and marking, amongst many others and provides a snapshot of the state of English language teaching today.